Socio-cultural Factors Affecting Fresh Fish Consumption and Willingness to Consume Fish-based Products among Tribals: A Study in Wayanad, Kerala - Radhakrishnan, Aparna; SAJEEV M. V.; A. K. Mohanty; Suseela Mathew; C. N. Ravishankar (Fishery Technology, 2023)
Fish consumption is a crucial component of a balanced and nutritious diet. The study identified the willingness to consume fish-based products and the socio-cultural factors affecting fresh fish consumption among the major tribes of Wayanad district in Kerala, South India. Sardine was the most consumed and favourite fish of the tribes, followed by mackerel. Variables like age and frequency of fresh fish consumption were found influencing the willingness of tribes for consumption of specific fish-based food products like fish soup, fish pappads, fish noodles, fish balls, and fish cutlets. The regression model revealed that factors including age, social media exposure, organizational trust, consumer trust, attitude of consumer, subjective norms, perceived behaviour control, and perceived risks of consuming fish affect the frequency of fresh fish consumption. The study indicates that the tribes of Wayanad prefer fresh fish over fish-based products and dried fish. The tribes expressed a willingness to consume fish-based products if provided free of cost, with fish soup, fish pappads, and fish noodles being the most preferred among a given set of options. The research highlights the need for policy interventions and extension efforts to promote fresh fish consumption, especially among tribal communities, to alleviate malnutrition.